PENGARUH ECONOMIC VALUE ADDED, MARKET VALUE ADDED, EARNING PER SHARE, DAN KEBIJAKAN DIVIDEN TERHADAP RETURN SAHAM PADA PERUSAHAAN GO PUBLIC DI BEI - Titik Purwanti (ITB AAS INDONESIA Surakarta, 2022)
The purpose of this study is to examine the effect of Economic Value Added, Market Value Added, Earnings Per Share, and Dividend Policy on Stock Returns in publicly listed companies on the IDX. Companies that are the focus of research are manufacturing companies. The data in the study includes the company's financial statements for three years in the 2018-2020 period. The sampling method used purposive sampling method with certain criteria so as to get as many as 55 manufacturing companies from the many manufacturing companies listed on the BEI. This study uses multiple linear regression analysis, with partial hypothesis testing, simultaneous testing, and the coefficient of determination. From the results of the research that has been done, the authors obtain results that show that there is a positive influence of EVA, MVA, EPS, and Dividend Policy on Stock Return. This happens because these manufacturing companies are able to create good performance so that investors can invest in the company with full confidence in both the security of their investment and the expected profit.